Global, regional, and national burden of neonatal sepsis and other neonatal infections attributable to low birth weight: a systematic analysis of deaths, and DALYs with predictions to 2031 - Jia, Xuelei; Sun, Xiaoxia; Wei, Kaifeng (Frontiers in Pediatrics, 2025)
BackgroundLow birth weight (LBW) is a leading risk factor for neonatal sepsis and other neonatal infections (NSNIs). However, the temporal and spatial trends in the global burden of NSNIs attributable to LBW have not been comprehensively estimated. This study aims to explore the global burden of NSNIs attributable to LBW from 1990 to 2021 and project future trends for the next decade.MethodsBased on data from the Global Burden of Disease (GBD) Study 2021, we analyzed the global burden of LBW-related NSNIs by the numbers of deaths and disability-adjusted life years (DALYs), and the corresponding age-standardized mortality rate (ASMR) and age-standardized DALYs rate (ASDR) by gender, Socio-demographic Index (SDI), region and country. Trends were quantified by the estimated annual percentage change, and future projections were made with the Autoregressive Integrated Moving Average (ARIMA) model to 2031.ResultsGlobally, there were approximately 136.83 thousand deaths and 12.31 million DALYs from NSNIs caused by LBW in 2021. From 1990 to 2021, the overall ASMR (2.75–2.21) and ASDR (247.28–198.94) per 100,000 population showed a downward trend. The burden was significantly higher in males than in females. Low and low-middle SDI quintiles had the highest burden, inversely related to SDI levels. Geographically, Western Sub-Saharan Africa and South Asia recorded the highest deaths and DALYs cases, while Central Europe and Australasia had the lowest. Projections indicate that by 2031, both ASMR and ASDR will continue to decline, expected to decrease by 11.49% compared to 2021.ConclusionAlthough the global burden of NSNIs attributable to LBW declined between 1990 and 2021, significant disparities persist, particularly among male neonates and in the Low SDI region, reflecting unequal access to healthcare. To mitigate the burden of LBW-related NSNIs, future efforts should prioritize enhancing targeted public health initiatives and healthcare interventions tailored to local contexts, while addressing the deficiency in health resource allocation and socioeconomic inequalities.